ODP.NET developer's guide Oracle Database 10g development with Visual Studio 2005 and the Oracle data provider for .NET : a practical guide for developers working with the Oracle data provider for .NET and the Oracle developer tools for Visual Studio 2005 - Pulakhandam, Jagadish Chatarji; Paruchuri, Sunitha; Safari eBooks (Birmingham [U.K.] : Packt Pub., 2007)
"This book is a practical guide that will give you the in-depth information you need to work with the Oracle 10g v10.2 database from Visual Studio .NET 2005, using the Oracle Developer Tools and ODP.NET"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Oracle (Computer file); Microsoft Visual studio; Microsoft .NET.; Electronic books